Eksploitasi Pekerja Anak: Kajian Terhadap Pekerja Anak di Sektor Perikanan - Irsan Irsan; Suparman Abdullah; Buchari Mengge (Mahesa Research Center, 2022)
The purpose of this research is to analyze the forms of exploitation of child labour in the fisheries sector and the resistance of workers to the exploitation they experience. The problem of this research is in the form of exploitation against child labour and resistance against child labour against exploitation experienced. To approach this problem, Collins' theory of exploitation and conflict is used as a reference. The data were collected through observation, in-depth interviews and documentation and analyzed qualitatively. Determining the informants using purposive sampling by the classification of the informants, namely the main informant of the employer and the informant who supports the family of child workers. The results showed that the forms of exploitation of child labour in the fisheries sector were violations of children's rights, namely labour exploitation (nipattolo-tolo), physical exploitation (nipattuju tedong), and mental exploitation (coto tena jenena). The form of child labour resistance to exploitation is carried out individually and in groups through. Exploitation that labours against child labour is not taken for granted, resistance to exploitation occurs in line with the experience and understanding of child labour towards the conditions of exploitation experienced.